The Impact of Formal Military Militias on the Democratic Transition Process in Post-2014 Iraq - Ibrahim, Shamall Ahmad; Amin, Abdulkarim Fattah; Kamaladdin, Nabaz Jamal; Agha Baba, Awat Muhammad; Mira, Ahmad Muhammad Rashid; Aziz, Aryan Sidiq (Universitas Islam Negeri Raden Intan Lampung, 2022)
One of the ways to the democratization process is through Military Forces. In this study, we identify and delve into the impact and influence of non-state armed groups on the democratization process in deeply divided societies, such as Iraqi society. At the beginning of the paper, we examine the Kurdish force (Peshmerga) and Shia armed groups (Popular Mobilization Forces – PMF) and assess their legal basis according to the Iraqi Post-2003 constitution. Furthermore, we will discuss in detail the role that these groups will play in strengthening and supporting a democratic transition. The main question in our research is to determine the role that these mentioned armed groups will play in Post-2014 Iraq, how they will contribute to preserving political stability, and also which position they will take in the democratic transition process. In this descriptive study, we employ an analytical approach to analyze the role of militias in Iraq, and a legal approach to explain the constitutional and legal articles that categorize these military forces as regular forces alongside the forces of the Iraqi Ministry of Defense. This research concludes that militias have a negative role in democratic transition, and countries must strive to dismantle these forces if they are not recognized as constitutional forces.